Logistics Performance, Industrialization, and Domestic Value Addition in Africa: Insights from a Dynamic Panel Analysis Emphasizing Egypt’s Role - Elshouqary, Noha Hassan; Ibrahiem, Dalia M.; Ragab, Ahmed (Journal of Ecohumanism, 2025)
This paper examines how logistics services influence Domestic Value Added (DVA) in seven African countries from 2000 to 2022. Using dynamic panel GMM analysis, results show that a one-unit increase in the Logistics Performance Index (LPI) leads to a 1% rise in DVA (p < 0.001), highlighting the role of efficient logistics in supporting economic growth. This is especially crucial for landlocked and less developed nations that rely on coastal countries for their exports. A 109,953.73 increase in manufacturing value added (MAUVA) is linked to a 1% rise in DVA, emphasizing the importance of industrialization. Egypt, a key contributor, exemplifies how structural changes support inclusive growth. Surprisingly, GDP per capita negatively correlates with DVA (−76.60), suggesting structural inefficiencies or import dependence. Conversely, population size positively affects DVA, indicating demographic advantages. These findings stress improving trade facilitation, logistics infrastructure, and industrial growth to enhance domestic value addition. They have policy implications for resilient growth in Africa, especially within initiatives like the African Continental Free Trade Area (AfCFTA).